2011
DOI: 10.1186/1471-2350-12-141
|View full text |Cite
|
Sign up to set email alerts
|

Mismatched single stranded antisense oligonucleotides can induce efficient dystrophin splice switching

Abstract: BackgroundAntisense oligomer induced exon skipping aims to reduce the severity of Duchenne muscular dystrophy by redirecting splicing during pre-RNA processing such that the causative mutation is by-passed and a shorter but partially functional Becker muscular dystrophy-like dystrophin isoform is produced. Normal exons are generally targeted to restore the dystrophin reading frame however, an appreciable subset of dystrophin mutations are intra-exonic and therefore have the potential to compromise oligomer eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…However, ITGA4 is highly expressed and important for immune cell function, therefore the exon skipping AOs identified from the fibroblast screen were further verified in the T lymphocyte cell line, Jurkat. Five AO sequences, H3A(+41 +65), H3A(+30 +49), H4A(+51 +75), H19A(+30 +49) and H27A(+20 +44) were synthesized as PMOs, as we have shown that these compounds conferred more robust splice switching in vitro and in vivo 20,21 . The rationale behind choosing these particular five AOs was to (i) compare the efficacy of PMO of different lengths [H3A(+41 +65) vs H3A(+30 +49)], (ii) confirm reduction of the full-length ITGA4 transcript, protein and activity observed after transfection with H4A(+51 +75), (iii) examine if modifying the AO backbone as a PMO could further increase the efficacy of H19A(+30 +49) in reducing ITGA4 protein levels and activity and (iv) ascertain if excision of the in-frame exon 27 would produce a soluble protein lacking the transmembrane domain encoded by that exon.…”
Section: Resultsmentioning
confidence: 99%
“…However, ITGA4 is highly expressed and important for immune cell function, therefore the exon skipping AOs identified from the fibroblast screen were further verified in the T lymphocyte cell line, Jurkat. Five AO sequences, H3A(+41 +65), H3A(+30 +49), H4A(+51 +75), H19A(+30 +49) and H27A(+20 +44) were synthesized as PMOs, as we have shown that these compounds conferred more robust splice switching in vitro and in vivo 20,21 . The rationale behind choosing these particular five AOs was to (i) compare the efficacy of PMO of different lengths [H3A(+41 +65) vs H3A(+30 +49)], (ii) confirm reduction of the full-length ITGA4 transcript, protein and activity observed after transfection with H4A(+51 +75), (iii) examine if modifying the AO backbone as a PMO could further increase the efficacy of H19A(+30 +49) in reducing ITGA4 protein levels and activity and (iv) ascertain if excision of the in-frame exon 27 would produce a soluble protein lacking the transmembrane domain encoded by that exon.…”
Section: Resultsmentioning
confidence: 99%
“…Splicing-targeted therapeutics has already shown a promise in treatment of disease. For example, induced exon skipping in Duchenne muscular dystrophy produces a “Becker muscular dystrophy-like dystrophin isoform,” successfully reducing disease severity [51]. One study has also demonstrated success using splice-switching oligonucleotides (SSO) to target HER-2 [52].…”
Section: Her-2 Variants As Clinical Targets?mentioning
confidence: 99%
“…Despite this similarity, one mutation responded to single exon skipping while the other required dual exon skipping to overcome the disease-causing mutation and restore the open reading frame. As we have found with other small dystrophin gene lesions, it appears that the various dystrophin splice site mutations will require personalized oligomer design and exon skipping strategies on a case-by-case basis (Forrest et al 2010 ; Fragall et al 2011 ; Adkin et al 2012 ).…”
Section: Introductionmentioning
confidence: 92%